Turbulent transport analysis of JET H-mode and hybrid plasmas using QuaLiKiz and Trapped Gyro Landau Fluid. (10th February 2015) - Baiocchi, B; Garcia, J; Beurskens, M; Bourdelle, C; Crisanti, F; Giroud, C; Hobirk, J; Imbeaux, F; Nunes, I; Contributors, JET
Abstract: The physical transport processes at the basis of JET typical inductive H-mode scenarios and advanced hybrid regimes, with improved thermal confinement, are analyzed by means of some of the newest and more sophisticated quasi-linear transport models: trapped gyro Landau fluid (TGLF) and QuaLiKiz. The temporal evolution of JET pulses is modelled by CRONOS where the turbulent transport is modelled by either QuaLiKiz or TGLF. Both are first principle models with a more comprehensive physics than the models previously developed and therefore allow the analysis of the physics at the basis of the investigated scenarios. For H-modes, ion temperature gradient (ITG) modes are found to be dominant and the transport models are able to properly reproduce temperature profiles in self-consistent simulations. However, for hybrid regimes, in addition to ITG trapped electron modes (TEM) are also found to be important and different physical mechanisms for turbulence reduction play a decisive role. Whereas E × B flow shear and plasma geometry have a limited impact on turbulence, the presence of a large population of fast ions, quite important in low density regimes, can stabilize core turbulence mainly when the electromagnetic effects are taken into account. The TGLF transport model properly captures these mechanisms and correctly reproduces temperatures.